2017
DOI: 10.1002/cctc.201700112
|View full text |Cite
|
Sign up to set email alerts
|

Direct Solid Lewis Acid Catalyzed Wood Liquefaction into Lactic Acid: Kinetic Evidences that Wood Pretreatment Might Not be a Prerequisite

Abstract: The objective of the present work was to determine if wood sawdust can be used instead of isolated cellulose in the general solid‐acid‐catalyzed production of chemicals. The kinetics of model cellulose and pine‐wood sawdust liquefaction into lactic acid were determined in the presence of a solid Lewis acid, ZrW. The catalytic hydrolysis of pine wood was performed at 190 °C in a large‐scale batch reactor (2.5 L). Similar kinetic curves of lactic formation were obtained for cellulose and wood as substrates. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, it has been proved that unlike in the case of fermentation, lignin present in the actual lignocellulose does not poison the chemocatalysts for the conversion of carbohydrates. 24 Unfortunately, only limited references are available, in which raw biomass is directly employed as the feedstock for LaA production. In the available literature, the yield of LaA directly from actual lignocelluloses (∼45%) without any pretreatment is considerably lower than that from pure cellulose even under severe conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, it has been proved that unlike in the case of fermentation, lignin present in the actual lignocellulose does not poison the chemocatalysts for the conversion of carbohydrates. 24 Unfortunately, only limited references are available, in which raw biomass is directly employed as the feedstock for LaA production. In the available literature, the yield of LaA directly from actual lignocelluloses (∼45%) without any pretreatment is considerably lower than that from pure cellulose even under severe conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared to commercial cellulose, results showed similar kinetic profiles indicated that the presence of other wood components like lignin did not affect the accessibility of the catalyst to the carbohydrate fractions (intrinsic hindrance), nor poison the active sites responsible for lactic acid formation. Moreover, a higher initial rate of product formation was observed from wood (Figure 7) certainly due to the different feature of cellulose (fiber morphology, lower crystallinity) and/or the contribution of hemicellulose in wood making its carbohydrate fraction more reactive [63]. Interestingly, it was shown by Infra-Red spectroscopy of the solid residue that the lignin component remained unchanged, certainly contributing to this result.…”
Section: Transformation Of Lignocellulosementioning
confidence: 93%
“…The reaction mechanism supposedly involves the presence of vacant Lewis sites at the surface of the catalyst able to promote dihydroxylation and carbon-carbon bond cleavages of the glucose chains in addition to hydride transfers giving pyruvaldehyde as intermediate [60]. Note that when lignocellulose was used as reactant in place of cellulose in same conditions, very close results were obtained, showing that the presence of other wood components may have no impact on the transformation of cellulose into lactic acid (see Section 4 for more details) [63]. When WO x -ZrO 2 or WO x -Al 2 O 3 served as support for Pt, and the transformation performed under H 2 , we observed the reduction of the intermediate to acetol and propylene glycol through successive hydrogenation steps (Scheme 3) [64,65].…”
Section: Transformation Of Cellulose In Watermentioning
confidence: 96%
“…Other Zn-, Zr-, and Nb-based Lewis acids have been recently reported to catalyze the conversion of cellulose and related carbohydrates to lactic acid in water [70][71][72][73][74][75][76][77] . Nevertheless, the efficiencies of these catalytic systems were generally not high (lactic acid yield < 35%) under hydrothermal conditions (453-573 K).…”
Section: Lewis Acidsmentioning
confidence: 99%